2020
DOI: 10.2147/cmar.s261828
|View full text |Cite
|
Sign up to set email alerts
|

<p>ANLN Directly Interacts with RhoA to Promote Doxorubicin Resistance in Breast Cancer Cells</p>

Abstract: Background: Chemotherapy resistance is the leading cause of cancer treatment failure. This research was conducted to explore a potential link between actin-binding protein anillin (ANLN) and doxorubicin resistance in breast cancer. Materials and Methods: We compared ANLN expression and 50% inhibition concentration (IC50) of doxorubicin in human breast cancer cells (MDA-MB-231) and human breast cancer cells with doxorubicin resistance (MDA-MB-231/ADM). Co-immunoprecipitation was used to investigate the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Despite a few molecular mechanisms involved in the process of doxorubicin resistance in cancer have been reported (Huang et al, 2018;Lovitt et al, 2018;Stefanski et al, 2019;Jin et al, 2020;Wang et al, 2020;Mirzaei et al, 2021;Yang et al, 2021), drug resistance is almost inevitable in advanced breast cancer patients, which remains a major unresolved issue in the treatment of cancer patients. An increasing number of studies have revealed that the alteration in chromatin accessibility plays a critical role in acquired resistance against cancer drugs (Jing et al, 2018;Zhang et al, 2020), but we still lack precise knowledge of how accessible chromatin state define transcriptional regulatory networks and which are the regulatory elements involved in doxorubicin resistance in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a few molecular mechanisms involved in the process of doxorubicin resistance in cancer have been reported (Huang et al, 2018;Lovitt et al, 2018;Stefanski et al, 2019;Jin et al, 2020;Wang et al, 2020;Mirzaei et al, 2021;Yang et al, 2021), drug resistance is almost inevitable in advanced breast cancer patients, which remains a major unresolved issue in the treatment of cancer patients. An increasing number of studies have revealed that the alteration in chromatin accessibility plays a critical role in acquired resistance against cancer drugs (Jing et al, 2018;Zhang et al, 2020), but we still lack precise knowledge of how accessible chromatin state define transcriptional regulatory networks and which are the regulatory elements involved in doxorubicin resistance in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, similar to TEAD4 , three of these genes ( ANLN , KRT6A , and RHOV ) were associated with poor outcomes in LUAD, which were all recognized as oncogenic genes. For instance, ANLN is a well-known oncogene that promotes carcinogenesis and therapeutic resistance in multiple types of cancers, such as LUAD ( Long et al, 2018 ; Xu et al, 2019 ; Deng et al, 2021 ), oral cancer ( Wang B et al, 2021 ), colorectal cancer ( Liu et al, 2022 ), breast cancer ( Wang et al, 2020 ; Maryam and Chin, 2021 ), pancreatic cancer ( Wang et al, 2019 ), and head and neck squamous cell carcinoma ( Guo et al, 2021 ). RHOV has been widely studied to promote LUAD cell growth, metastasis, and therapeutic resistance ( Chen H et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was reported that ANLN promoted pancreatic cancer progression by regulating EZH2/miR-218-5p/LASP1 signaling axis 15 . ANLN promoted doxorubicin resistance in breast cancer cells by activating RhoA 16 . ANLN played a critical role in human lung carcinogenesis through the activation of RHOA and by involvement in the phosphoinositide 3-kinase/AKT pathway 17 .…”
Section: Introductionmentioning
confidence: 99%